A SYSTEMATIC STUDY OF AI ADOPTION IN ACCOUNTING: AUTOMATING PROCESSES, REDUCING ERRORS, AND ENHANCING DISCLOSURE QUALITY - Lec. Nejoom Taher; Hanaa Mathboob; Sabreen Balasim (Scholar Express Journals, 2024)
This paper tries to focus on AI in the accounting sector, its applications (current and prospective), advantages, difficulties and impacts. It is structured as follows. Literature Review: In the first stage many related works considered to ensure the state, potential applications and challenges of Artificial Intelligence in Accounting. Systematic Review: Second stage, Impact of AI implementation towards the accounting processes, monitoring changes and trends. Comparative Review: Most researches are compared at third stage in order to assess the variety of views on the effects of AI and the areas of investigation remain uncovered. The implementation of AI evidently has a lot of advantages like bringing in more transparency, accuracy and efficiency as well as much more complex analytical abilities. For a more in-depth analysis of the underlying topics, e.g. seminal tracking studies and mediators/moderators, sociotechnical impacts, cultural factors as well as preparedness for digital transformation, and ethical dilemmas related to use of intelligent transportation systems are all presented or brought forth. Future research should focus on the application of AI in early-adopting nations especially those lagging behind, along with efforts to develop accounting systems to attain a global balance in AI research.
Keywords: financial accounting; Accounting; disclosure quality